The Strategic Role of Nuclear Energy in Supporting the Clean Energy Transition Toward Net Zero Emission - Khairah, Muzayyanah Zul; Burhanuddin, Husnul Faihah; Tang, Zulfiani; Aslim, Muhammad Arief Fitrah Istiyanto (Pinisi: Physics Journal, 2025)
The transition to clean energy is an urgent global agenda to address climate change and fulfill Net Zero Emission (NZE) commitments, including in Indonesia which targets NZE by 2060. This article analyzes the strategic role of nuclear energy as a low-carbon energy source in supporting the clean energy transition. A literature review of the latest scientific sources discusses the basic principles of nuclear physics in fission reactions, the advantages of nuclear energy over fossil energy in reducing carbon emissions, and the challenges and prospects for developing nuclear technology. The analysis shows that nuclear energy has significant potential to substantially reduce carbon emissions, ensuring energy supply security, and acting as a complement to intermittent renewable energy sources. However, safety issues, radioactive waste management, and initial investment costs are still major challenges that require technological innovation and strict regulations. Thus, nuclear energy deserves to be considered a key pillar in Indonesia's decarbonization strategy and achievement of NZE, provided that it is accompanied by continuous efforts to improve safety standards and risk management.